2020
DOI: 10.1002/bmc.5029
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification in human blood serum of the proteins possessing the ability to bind with 48 kDa form of unconventional myosin 1c and their possible diagnostic and prognostic value

Abstract: We firstly identified 48 kDa molecular form of the unconventional myosin 1c (p48/Myo1C), and isolated it from blood serum of multiple sclerosis patients. The amount of p48/Myo1C in human blood serum correlated with some autoimmune, hemato‐oncological and neurodegenerative diseases and thus may serve as a potential molecular biomarker. The biological functions of this protein in human blood remain unknown. Previously, we used the monodisperse magnetic poly (glycidyl methacrylate)(mag‐PGMA–NH2) microspheres with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It is known that Myo1C (molecular mass 121.7 kDa) is abundantly expressed in mammalian B lymphocytes [12] and the level of 48 kDa fragment in blood serum could be tightly associated with blood cells degradation [11,12,17]. Further investigation demonstrated that 48 kDa myosin 1C capable of binding in blood serum with IgG and IgM immunoglobulins [18], as well as with component 3 of the complement and the antithrombin-III [19]. Thus, we suggest that 48/Myo1C might be engaged in immunologic and coagulation cascades in the bloodstream of COVID-19 suffering patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that Myo1C (molecular mass 121.7 kDa) is abundantly expressed in mammalian B lymphocytes [12] and the level of 48 kDa fragment in blood serum could be tightly associated with blood cells degradation [11,12,17]. Further investigation demonstrated that 48 kDa myosin 1C capable of binding in blood serum with IgG and IgM immunoglobulins [18], as well as with component 3 of the complement and the antithrombin-III [19]. Thus, we suggest that 48/Myo1C might be engaged in immunologic and coagulation cascades in the bloodstream of COVID-19 suffering patients.…”
Section: Resultsmentioning
confidence: 99%
“…Coronavirus disease 19 (COVID- 19) is a global health crisis, where SARS-CoV-2 is the novel coronavirus responsible for this respiratory disease. COVID-19 has different manifestation.…”
Section: Introductionmentioning
confidence: 99%
“…We have detected this product of degradation of the Myo1C in the severe Covid-19 patients and showed that its level in those patients was significantly higher than in healthy human individuals. Recently, we revealed a capability of binding of 48/Myo1C to component 3 of the complement system and to anti-thrombin III of the coagulation cascade ( Starykovych et al, 2021 ). Thus, the pathogenic action of 48/Myo1C can involve complement system and coagulation cascade that are heavily disturbed in patients with severe Covid-19.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we used affinity chromatography on the magnetic poly(glycidyl-methacrylate) (mag-PGMA–NH 2 ) microparticles functionalized with Myo1C and MALDI–TOF mass spectrometry with molecular modeling in silico in order to identify potential molecular partners of the 48/Myo1C. It was found that 48/Myo1C might bind to component 3 of the complement system and the anti-thrombin-III ( Starykovych et al, 2021 ). Thus, the mechanisms of the pathogenic action of truncated form of Myo1C in severe COVID-19 patients may involve a suppression of the immune cells, as well as modulation of complement and coagulation cascades.…”
mentioning
confidence: 99%
“…Our preliminary data suggest that increasing of the level of 24.0 kDa proteins and the appearance of 52.0 kDa proteins in human urine might be associated with the appearance of the decompensated stage of liver cirrhosis. However, the assessment of their diagnostic value needs further studies [14]. This fact suggests that the distribution of cortactin molecular forms in the urine might have a diagnostic and/or prognostic significance.…”
mentioning
confidence: 99%